Trade agreements and subnational income of border regions - Hanna L. Adam; Mario Larch; David Stadelmann (Economic Inquiry, 2023)
This paper analyses the differential effect of trade agreements on income per capita of subnational regions with international borders. We construct an extensive panel dataset covering 1350 regions in 86 countries worldwide between 1950 and 2017. Our results show that trade agreements are positively associated with income per capita of regions sharing contiguous borders with trading partners, relative to regions sharing borders with countries with whom no trade agreements exist. For border regions, the positive relationship of trade agreements and regional income roughly compensates potential income disadvantages of having international borders. These insights help in explaining and mitigating regional inequalities.
Keywords: 330; GDP per capita; regions with international borders; subnational analysis; trade agreements